CARE TRAJECTORY AS A METHODOLOGICAL STRATEGY IN TEACHING AND UNIVERSITY EXTENSION: EXPERIENCE REPORT: Care Trajectory as a Methodological Strategy - Souza Gleriano, Josué; Gomes Ludwig, Monylla; Keren Alves Rodrigues, Whagda; de Oliveira Barbosa, Vinícius; Gomes Santanna Dantas, Hellen; Jaqueline Feix Rodriques, Dienefer (Journal of Health Care, 2024)
Introduction: Educating professionals engaged with their social reality is an institutional commitment. Objective: To describe the contributions of the adoption of the care trajectory as a methodological strategy for teaching and university extension, with a view to understanding the benefits of this approach in academic training. Method: Experience report with document analysis and reflective narrative review on the use of the care trajectory in teaching and university extension from the experience in a public university in the state of Mato Grosso, involving students, professors, and health professionals, in the period 2021-2023. Students and extension workers carried out home visits to collect care trajectories, following specific criteria and a structured script. The analysis was based on citizenship training and co-management. Results: The care trajectory is an innovative and effective methodological strategy for university teaching and extension in the field of health and its adoption promoted contextualized learning and the development of interdisciplinary skills. The practice enabled an in-depth understanding of the guidelines of the Unified Health System and the reality of users, facilitated the analysis of critical points in the health system and the formulation of interventions, reinforcing the need for co-management and interprofessional collaboration for the continuous improvement of access to health services. Conclusion: The care trajectory benefits teaching and university extension as a methodological strategy, contributed to contextualized learning, but for social transformation requires a critical and reflective approach through co-management.